Environmental Enrichment and Physical Exercise Attenuate the Depressive-Like Effects Induced by Social Isolation Stress in Rats - Brenes, Juan C.; Fornaguera, Jaime; Sequeira-Cordero, Andrey (Frontiers in Pharmacology, 2020)
We assessed the antidepressant-like effects of environmental enrichment (EE) and physical exercise (PE) compared with the selective serotonin reuptake inhibitor fluoxetine against the depression-related neurobehavioral alterations induced by postweaning social isolation (SI) in rats. After one month of SI, rats were submitted to PE (treadmill), EE, or fluoxetine (10 mg/Kg), which were compared with naïve SI and group-housed rats. After one month, behavior was analyzed in the open field (OFT), the sucrose preference (SPT), and the forced swimming (FST) tests. Afterward, the hippocampal serotonin contents, its metabolite, and turnover were measured. SI induced a depression-related phenotype characterized by a marginal bodyweight gain, anxiety, anhedonia, behavioral despair, and alterations of serotonin metabolism. EE produced the widest and largest antidepressive-like effect, followed by PE and fluoxetine, which were almost equivalent. The treatments, however, affected differentially the neurobehavioral domains investigated. EE exerted its largest effect on anhedonia and was the only treatment inducing anxiolytic-like effects. Fluoxetine, in contrast, produced its largest effect on serotonin metabolism, followed by its anti-behavioral despair action. PE was a middle-ground treatment with broader behavioral outcomes than fluoxetine, but ineffective to reverse the serotonergic alterations induced by SI. The most responsive test to the treatments was the FST, followed closely by the SPT. Although OFT locomotion and body weight varied considerably between groups, they were barely responsive to PE and fluoxetine. From a translational standpoint, our data suggest that exercise and recreational activities may have broader health benefits than antidepressants to overcome confinement and the consequences of chronic stress.